Activities of Diplomatic Corps of Lithuania between 1940–1941 - Jonušauskas, Laurynas (Genocidas ir rezistencija, 1999)
After the Soviet occupation of Lithuania on June 15, 1940, the diplomatic corps of Lithuania became the only institution which de jure represented Lithuania abroad and made all possible efforts to re-establish its independence. During July–August of 1940, Lithuania's diplomats abroad lodged protests against the occupation of Lithuania to the states they were accredited at and to the Ministry of Foreign Affairs of Lithuania. In the autumn of 1940, Lithuanian diplomats held two meetings: one in Rome and another in Bern. Antanas Smetona, the President of Lithuania, participated in one of them. After the meeting in Rome the corps established the National Committee. The Committee was to coordinate political actions of liberation abroad. At the meeting in Bern President Smetona signed the Kybartai Act. Unfortunately, neither the National Committee nor the Kybartai Act, had any significant impact on the fight for freedom of Lithuania. The activities of the diplomatic corps had been hampered by a number of factors: first of all, it greatly depended on the situation in Europe at that time (the aggressive policy of the Soviet Union and Germany), the uncertain status of the corps itself, the difficulties in maintaining communication and, finally, the differences of views among the diplomats towards the problems of the day.